Aquisição da escrita: implicações do outro - Silva, Joelma Oliveira Santos (2016)
For a long time, I have worked in school as a teacher of children in the early grades of elementary school. During my practice in the classroom, a question has always caught my attention: how does the acquisition of writing by children happen, mainly of those who do not ascend to writing in the period, according to the official documents, is expected that such acquisition occurs? Out of this concern, the research project "Writing Acquisition: Implications of the Other" arose, presented to the Postgraduate Teaching Program in Basic Education of Applied Teaching and Research Center for Education (PPGEEB / CEPAE / UFG) which resulted in the present work. To conduct my investigation on this subject, I took as theoretical referential the Lacanian and the Freudian psychoanalysis. Among the psychoanalytic notions that guide my study, there is the "Other", essential instance for the constitution of subjectivity. I also used the operations of "alienation" and "separation", such as developed by Jacques Lacan (2008), to analyze the written production of students who, according to their age, should have been literate, handling with 'ease' the written standard, but still do not. The written productions were the result of workshops specifically designed for these children. Beyond these productions, I analyzed interviews and questionnaires which were conducted by the manager and pedagogical group of the school and also by those responsible of the students. The research took place in a regular educational institution since this is the privileged place in which writing and reading are formally presented to the child. My hypothesis is that this is the right time for pedagogical interventions to be carried out in order to avoid social constraints to these children due to the fact that they are not literate.